1999
DOI: 10.2527/1999.771180x
|View full text |Cite
|
Sign up to set email alerts
|

Processing, mixing, and particle size reduction of forages for dairy cattle.

Abstract: Adequate forage amounts in both physical and chemical forms are necessary for proper ruminal function in dairy cows. Under conditions in which total amounts of forage or particle size of the forage are reduced, cows spend less time ruminating and have a decreased amount of buoyant digesta in the rumen. These factors reduce saliva production and allow ruminal pH to fall, depressing activity of cellulolytic bacteria and causing a prolonged period of low ruminal pH. Insufficient particle size of the diet decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 17 publications
3
59
1
10
Order By: Relevance
“…Effects of feeding corn silage of reduced particle size to lactating dairy cows on consumption of different size particles as described by the Penn State Particle Separator. of over 5000 samples, Heinrichs et al (1999) reported that on average corn silage samples fed on commercial dairy farms contain 8.1 ± 6.4% of the DM greater than 19.0 mm, but variation across herds is large. In the same survey, a minimum of 1% and a maximum of 81% of DM was >19.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of feeding corn silage of reduced particle size to lactating dairy cows on consumption of different size particles as described by the Penn State Particle Separator. of over 5000 samples, Heinrichs et al (1999) reported that on average corn silage samples fed on commercial dairy farms contain 8.1 ± 6.4% of the DM greater than 19.0 mm, but variation across herds is large. In the same survey, a minimum of 1% and a maximum of 81% of DM was >19.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a survey composed of over 800 samples, Heinrichs et al (1999) reported that although TMR samples fed on commercial dairy farms typically contain 7% of the particles greater than 19.0 mm variation across herds is large. In the same study, a minimum Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Across treatments peNDF values were not different and averaged 31.6 (Table 4). In a survey evaluating TMR physical form (n = 831 samples), Heinrichs et al (1999) reported that TMR samples fed on commercial dairy farms typically contain 7, 35, and 58% of the material retained on the 19-and 8-mm sieves, respectively. In the same study a minimum of 1.1 and a maximum of 43.1% was observed on the 19-mm sieve, while a minimum of 2.4 and a maximum of 69.1% was retained on the 8-mm sieve.…”
Section: Ration Particle Size and Effective Fiber Measurementsmentioning
confidence: 99%